If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3 + -1t) + -1(3 + -3t) = 5 (3 * 5 + -1t * 5) + -1(3 + -3t) = 5 (15 + -5t) + -1(3 + -3t) = 5 15 + -5t + (3 * -1 + -3t * -1) = 5 15 + -5t + (-3 + 3t) = 5 Reorder the terms: 15 + -3 + -5t + 3t = 5 Combine like terms: 15 + -3 = 12 12 + -5t + 3t = 5 Combine like terms: -5t + 3t = -2t 12 + -2t = 5 Solving 12 + -2t = 5 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -2t = 5 + -12 Combine like terms: 12 + -12 = 0 0 + -2t = 5 + -12 -2t = 5 + -12 Combine like terms: 5 + -12 = -7 -2t = -7 Divide each side by '-2'. t = 3.5 Simplifying t = 3.5
| 8x^6+6x^3+7=0 | | 3x+11=25 | | r^2-15r+54=0 | | 4x+10y-8+4x-4y= | | x^2-x-110=0 | | 10-a+3a=6 | | 3n+8= | | 2*-8.5+13.6=0.5*-8.5 | | 3(7-y)-6*2=-21 | | 2.3g=7013 | | 5x+6a+7= | | 2x+.25x=54 | | 12w-8=28 | | 2x+13.6=0.4x | | 23a=30 | | 3x-7x+4= | | 8k+7k=0 | | 4(w+7)-(-3w-9)=6w | | 7.5x-1.5x=6.6 | | 29x^2-12x=0 | | m^2-24m=-144 | | 3x^2-7x+12=0 | | 4(4y+2)=(1+6y)+8 | | 4(z-5)+2=x+3 | | 11x-14y=13 | | -5z-9=-24 | | 3x+9=9x-21 | | 25x^3-20x^2+20x-16= | | 156=50+w | | x+16=2(4x+8) | | Y-0.6=2(x-0.8) | | 0=x^2-29x-108 |